Genome Sequence of Rickettsia conorii subsp. indica, the Agent of Indian Tick Typhus - Sentausa, Erwin (American Society for Microbiology, 2012)
Rickettsia conorii subsp. indica is the agent of Indian tick typhus. The present study reports the draft genome of Rickettsia conorii subsp. indica strain ITTR (ATCC VR-597).